Low molecular weight chitosan attenuates acrylamide-induced toxicity in Drosophila melanogaster - Swetha Senthil Kumar; Sahabudeen Sheik Mohideen (Toxicology Reports)
Acrylamide (ACR), a toxic by-product of high-temperature food processing, poses significant health risks due to its oxidative, neurotoxic, and genotoxic properties. Regulatory measures focus on limiting ACR in commercial food products, yet daily cooking practices often result in unnoticed exposure, threatening vulnerable populations such as children. This study evaluates the protective role of low and medium molecular-weight (MW) chitosan against ACR-induced toxicity using Drosophila melanogaster. Chitosan, a natural polysaccharide with antioxidant and prebiotic properties, was supplemented alongside ACR exposure in larvae and adult flies. Developmental metrics such as pupation rates, fecundity, and adult emergence were assessed, alongside oxidative stress markers and neurobehavioral outcomes. ACR exposure impaired development, increased oxidative stress, and reduced locomotor activity. Supplementation with low and medium MW chitosan alleviated these effects, with low MW chitosan demonstrating greater efficacy. These findings reveal the potential of low MW chitosan as a dietary intervention to counteract the toxic effects of contaminants like ACR. By reducing oxidative stress, preserving mitochondrial function, and supporting developmental processes, chitosan offers a promising avenue for mitigating the overall toxicity of heat-processed toxins. These findings further highlight chitosan's molecular weight-dependent protective potential against ACR toxicity, offering insights into its application as a dietary mitigator of heat-processed toxins.